Levetiracetam-Induced Acute Psychosis in an Adolescent - Dhungel, Omkar; Shrestha, Amit; Pathak, Pankaj; Sharma, Pawan (Case Reports in Psychiatry, 2023)
Levetiracetam (LEV), a second-generation antiepileptic, is used as an adjunct therapy in primary generalized tonic–clonic seizures, refractory partial-onset seizures, and seizure prophylaxis after brain surgery. It is well tolerated, effective and has a convenient dosing regimen. As any other drugs, it has some adverse drug effects, including neuropsychiatric adverse effects ranging from agitation and mood symptoms to psychosis and suicide. Strong diagnostics guidelines are yet to be formulated for LEV-induced psychosis; however, complete recovery from psychotic symptoms after stopping LEV supports the possible adverse reaction from Naranjo’s algorithm and, hence, the diagnosis. This case report presents a 16 years boy with focal onset generalized tonic–clonic seizure, whose drug regimen was switched to LEV, following which he had the delusion of persecution, second-person auditory hallucination, and aggressive behavior, which decreased on the 2nd day of cessation of LEV.